STRATEGI GURU DALAM MEMBELAJARKAN MATEMATIKA PADA SUB POKOK BAHASAN SIFAT-SIFAT BANGUN DATAR KEPADA ANAK TUNARUNGU - Hidayati, Herlina (Journal of Mathematics and Mathematics Education, 2012)
Â ABSTRACTDeaf children are those who lose their auditory capability, both, partly or completely causing their auditory sense has no functional value in daily life. Accordingly, with this condition, they will experience difficulty in a learning process. Therefore, special learning strategy is needed to teach mathematics to deaf children and scaffolding can be used to help students who have difficulties. A learning strategy is a way that will be selected and used by a teacher to deliver learning material so that it will facilitate learner in achieving an expected learning goal. A learning strategy covers method, technique, and tactic in a process of learning. Whereas, scaffolding is supports provided in each stage of learning and problem solving. Purpose of the research is to describe a teacherâs ways of teaching learning material of flat structure and how does a teacher provide scaffolding to deaf students of class V of SLB-B YRTRW of Surakarta who have difficulty in working on exercise problems.The research is a descriptive-qualitative research with case study approach. Sample is taken by using purposive random sampling technique. The subjectÂ  research of this study is a fifth grade mathematics teacher SLB-B YRTRW of Surakarta. Data is collected by using observation and interview. Data of the researchâs result is analyzed by using Miles and Huberman model.The results showed that the strategy used teacher in mathematics learning of the subject sub properties built flat which includes the use of methods and techniques look the same as learning in school in general, but in terms of tactics look very different. Teachers use a variety of tactics such as opening the lesson teacher led prayer gestured with hands clapped over and over again. Having students collect homework by standing in front of students and to repeat what hes talking about. Roll students by asking the other students by appointing a bench of students who do not belong to clarify the expression on her speech. Appoint students who have not focused attention on the lesson with the student approached and patted him then give the question. Train students to speak by pointing and other students to give examples if still canât approach the teacher and students are trained to speak directly with speech and expression made it clear repeatedly. Asking questions about the last lesson by holding up a flat image was then shown to the students with a straight face talking all that clarified and the question was asked repeatedly followed gesture. Deliver the learning objectives in a way it slowly with expression speak to clarify and say it repeatedly. When the core lessons teachers deliver the material to write the title and the drawing up on the board by providing a detailed description of the image. Introduce a flat up by showing a picture and then pointed to the writing on the blackboard. Images shown in the direction of all students by holding the picture. Conduct debriefing with the students by providing questions to the students by using a flat image and up to students who canât speak with the teacher asking questions and the question was asked how to deal repeatedly with clear expression and speech writing problem on the board. Introduce the opposite side and a flat pair up with examples in actual practice in daily life by having four students come forward and form a position opposite and pair up with to explain to students that is opposite and in pairs they practice it as such. When closing the lesson the teacher to make conclusions lesson by guiding students to repeat the lesson by standing next to the blackboard and pointing fingers properties that have been written. Give homework to students, the given problem is a problem that already exists at student worksheets but the teacher wrote the book back on the board and page numbers matter. While the teacher in providing scaffolding for students who have difficulty in doing the practice questions by writing them back problem on the board and having students read back the question by pointing to questions over and over again. For students who do not understand about the teacher highlights the core problem that has been written in the book and give examples of students. Guiding students individually to check students work by giving you step-by-step work coherently to give an example to measure, draw and annotate a complete picture. When finished working on the teacher invites students to discuss the matter with one of the students pointed forward or just by reading about the matter by pointing at the book and then the students respond orally.Key words: learning strategies, scaffolding, learning mathematics, the properties of a flat wake, hearing impairment.